Allergy – current insights into prevention and diagnostic workup of immediate‐type allergy and treatment of allergic rhinoconjunctivitis. (27th July 2015) - Brehler, Randolf; Stöcker, Benedikt; Grundmann, Sonja
Summary In recent decades, the incidence of allergic diseases has dramatically increased, by now affecting a large percentage of the population. For a long time, allergen avoidance was considered the most crucial measure in primary allergy prevention. However, studies have increasingly shown that exposure to allergens is an essential prerequisite for the development of immunological tolerance. Diagnostic workup is based on patient history, skin tests, and measurement of specific IgE antibodies. The introduction of component‐based diagnostic workup offer an option to differentiate between primary sensitization and cross‐reactivity caused by sensitization to panallergens or sensitization to cross‐reactive carbohydrate epitopes. Symptomatic treatment only leads to temporary relief of allergic symptoms. By contrast, specific immunotherapy (SIT) may have long‐lasting therapeutic effects and potentially even result in a complete cure. The selection of allergens for SIT is guided by the principle of major allergens. It is recommended to use those preparations that have been proven safe and effective in controlled clinical studies. With respect to subcutaneous immunotherapy, a host of tested and approved extracts are available for a wide range of different allergens. Large clinical trials have also confirmed the efficacy of sublingual immunotherapy with grass and also birch pollen extracts, which has led to the official approval of some preparations containing these allergens.